2019
DOI: 10.1024/0300-9831/a000413
|View full text |Cite
|
Sign up to set email alerts
|

No Difference in Magnesium Intake between Obese Women and Healthy Controls

Abstract: Abstract. Magnesium is a predominantly intracellular ion and plays an important role in energy metabolism and in the maintenance of energy homeostasis. This study aimed to estimate the dietary intake of magnesium and its association with adiposity parameters in obese women. This cross-sectional study included 125 women, aged between 20 and 50 years, who were divided into two groups: obese group (n = 62) and control group (n = 63). The control group was age-matched. Adiposity parameters determined were weight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
1
Order By: Relevance
“…Another study using data from the National Health and Nutrition Examination Survey also found that magnesium intake was negatively correlated with BMI and WC ( 43 ) . In contrast, another study found no association in magnesium intake between obese women and healthy controls ( 44 ) , which contrasts with our findings. However, as we have mentioned, although previous studies have found negative associations between certain micronutrient intake and obesity, it does not necessarily mean that micronutrient deficiency is more prevalent among obese individuals.…”
Section: Discussioncontrasting
confidence: 99%
“…Another study using data from the National Health and Nutrition Examination Survey also found that magnesium intake was negatively correlated with BMI and WC ( 43 ) . In contrast, another study found no association in magnesium intake between obese women and healthy controls ( 44 ) , which contrasts with our findings. However, as we have mentioned, although previous studies have found negative associations between certain micronutrient intake and obesity, it does not necessarily mean that micronutrient deficiency is more prevalent among obese individuals.…”
Section: Discussioncontrasting
confidence: 99%